Skrining Fitokimia Dan Uji Aktivitas Antioksidan Ekstrak Buah Kupa (Syzygium polycephalum) Dengan Metode 1,1-diphenyl-2-picrylhydrazil - dharmayanti, Luky; Jannah, Syauqul; Oktamauri, Ariesa (Poltekkes Kemenkes Bengkulu, 2025)
Kupa fruit has a high anthocyanin content and is useful as an antioxidant. Phytochemical screening shows flavonoid compounds in the skin and fruit. Free radical damage to skin cells can be repaired using antioxidants, because antioxidants can kill and neutralize radicals in the body so that oxidative stress and cell damage can be avoided. The purpose of this study was to determine the value of antioxidant activity and antioxidant content of kupa fruit extract (Syzygium polycephalum). This study used kupa fruit extract (Syzygium polycephalum) This will be examined using the 1,1-diphenyl-2-picrylhydrazyl technique to determine its antioxidant activity. A UV-Vis spectrophotometer was used to detect absorbance at λ 517 nm. The results are represented as IC50 (Inhibitory Concentration) values, which indicate the concentration of antioxidant substances that capture 50% of DPPH radicals. Kupa fruit extract has an extract yield of 40.11% and is positive for alkaloid, flavonoid, and tannin components, according to phytochemical screening results, the water content is 30.65% and the ash content is 1.13%. The results of the antioxidant activity test of kupa fruit extract show a relatively strong IC50 value of <100 µg/mL with an IC50 value of 99.74. Keywords: Kupa fruit (Syzygium polycephalum), antioxidant, DDPH, IC50